The social buffering of pain by affective touch: a laser-evoked potential study in romantic couples. Issue 11 (24th September 2018) - von Mohr, Mariana; Krahé, Charlotte; Beck, Brianna; Fotopoulou, Aikaterini
Abstract: Pain is modulated by social context. Recent neuroimaging studies have shown that romantic partners can provide a potent form of social support during pain. However, such studies have only focused on passive support, finding a relatively late-onset modulation of pain-related neural processing. In this study, we examined for the first time dynamic touch by one's romantic partner as an active form of social support. Specifically, 32 couples provided social, active, affective ( vs active but neutral) touch according to the properties of a specific C-tactile afferent pathway to their romantic partners, who then received laser-induced pain. We measured subjective pain ratings and early N1 and later N2-P2 laser-evoked potentials (LEPs) to noxious stimulation, as well as individual differences in adult attachment style. We found that affective touch from one's partner reduces subjective pain ratings and similarly attenuates LEPs both at earlier (N1) and later (N2-P2) stages of cortical processing. Adult attachment style did not affect LEPs, but attachment anxiety had a moderating role on pain ratings. This is the first study to show early neural modulation of pain by active, partner touch, and we discuss these findings in relation to the affective and social modulation of sensory salience.